Thermal Comfort Improvement for Atrium Building with Double-Skin Skylight in the Mediterranean Climate - Sokkar, Refaa; Alibaba, Halil Z. (Mdpi, 2020)
Atria are added to buildings for their aesthetical, environmental, and economic benefits; the appropriate atrium design can enhance an atrium's thermal performance and the adjacent spaces' temperatures. However, inappropriate design decisions cause thermal discomfort and consequently, higher energy consumption. Since the Mediterranean climate has diverse climatic conditions around the year, a central atrium with a top-lit skylight is recommended, but during the summer period it can cause overheating, and the insertion of shading elements shrinks the lighting performance: thus, the atrium skylight design is supposed to improve thermal comfort without affecting the lighting level. This study investigated the improvement of thermal performance in the atrium building by the implementation of a double-skin skylight (DSS) to enhance the atrium thermal performance without shading. The research conducted computer simulations with Environmental Design Solutions (EDSL) Tas software sequentially. The study prepared various design strategies, and different proposals were tested and compared in terms of indoor temperatures, with reference to American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE-55). The implementation of DSS achieved an average of 77% comfort in working hours around the year with different opening percentages according to the outdoor conditions. Moreover, results show that changing the DSS glazing materials did not affect the thermal performance of the atrium.
Keywords: atrium; natural ventilation; thermal comfort; passive design strategy; Mediterranean climate; double skin skylight